IDENTIFICATION OF VITAMIN C IN FLOWERS AND LEAVES MALUS SPP. - Inna V. Goncharovska; Vladimir F. Levon; Vladimyr V. Kuznetsov; Galina O. Antonyuk (Химия растительного сырья, 2022)
The objective of this study was to evaluate the ascorbic acid content in vegetative and generative organs of crabapple from the collection of the M.M. Gryshko National Botanical Garden of National Academy of Sciences of Ukraine. Considering the abundant flowering, higher fruiting in comparison with Malus domestica Borkh., increased content of nutrients and biologically active substances in flowers and leaves of crabapple, they deserve wide use in production. The genotypes were planted to a permanent place of growth in 2014. Total ascorbic acid content in flowers ranged from 116 (Holliana) to 188 (Era) mg / 100 g, in leaves from 112 (Van Ezeltin) to 183 (Royalty) mg / 100 g.The objects of the study are valuable for use as raw materials of biologically active additives. Using the flowers and leaves of Malus spp., As raw materials for the production of dry powder, will meet the needs of consumers for affordable and nutritious ingredients rich in vitamin C.